Solubility of Carbon Dioxide (C02) From Natural Gas Using Various Types of Amine - Based Compounds - Emy Marlina Binti Samsudin, Emy Marlina (Universiti Teknologi Petronas, 2009)
This final report emphasized on the project title "Selectivity of Carbon Dioxide ((: O, ) Removal in Natural Gas Using Various Type of Amine-Based Compound. It consist multiple sections ranging from project background, literature review, methodology, results and discussion and conclusion. The objective of this project is to evaluate the solubility of carbon dioxide in various amine compounds by performing laboratory experiments (batch process), using various amine mixtures and ratios, manipulated system temperature and carbon dioxide partial pressure. These amine-based compounds include secondary and tertiary amine mixtures, where methyethanolamine (MDEA) is supported by a promoter or activator. The equipment setup for the laboratory analysis involves High Pressure Gas Solubility Cell (MODEL BP 22). This equipment has been designed for measurements of gas solubility in liquid at high pressure and temperature. The unit is capable of determining the solubility of gases in various liquid, effect of temperature and pressure on the component solubility, formation of methane hydrate and other complexes under high pressure and reduction of solubility after repeated solution stripping cycle. Also included in this report are the experiment layouts and the calculations involved in preparing the desired amine solutions.